THE «RODINA» CONCEPT AS A COMPONENT OF THE NATIONAL IMAGE OF RUSSIA IN THE RUSSIAN LANGUAGE PICTURE OF THE WORLD - A. К. Perevoznikova (Концепт: философия, религия, культура, 2019)
In conceptosphere “the national image of Russia» the concept “Rodina” occupies a key place in the Russian language picture of the world and represents the unity of linguistic and cultural content. This article is devoted to the analysis of language, spheres that represent the concept of a motherland in Russian linguistic picture of the world. With a view to lingvoсulturological conceptual description area birthplace can be represented as a structure that defnes the base for Russian culture constant native earth («rodnaya Zemlya»), dating back to ancient mythological archetypes such as mother earth, motherland, Terra Mater. This image was fxed in proverbs and sayings, and today has a sacral meaning associated with a woman as the ascetic nature and nation. This topic is also relevant in the minds of modern Russian language media, as evidenced by the data of the Russian Association of the dictionary. Meaningful concept structure is updated in the nuclear sense: “native land as geographic Wednesday habitats”, “Patria”, “little homeland”, “perceptions and attitudes towards their motherland”, shaped, metaphorical redefning of this concept. When considering the linguistic representatives of the concept “Rodina” diachronically, the evolution of its content is traced. The process of evolution is the accumulation of conceptual signs as a result of the movement of this concept from nature-ethnic-religious through ethical and civic notions of homeland to the idea of national identity through the history, religion, language and literature. In the article it is illustrated by proverbs and sayings and by the examples from fction. Content and use of tokens belonging to the “patriotic triad” – motherland, fatherland, native country – is considered in diachronic. In the modern Russian discourse the interpretation of the concept of “motherland” appeared to be wide and varied, creating polyphonism of evaluations and interpretations of its content in the minds of Russian language media, supported by verses of classics and modern Poets.